ICT adoption and its influence on economic growth and innovation - Let, Halimahton Sa'diah (2020)
The rapid growth of Information and Communication Technology (ICT) has been found to be an important element in enhancing countries’ economic growth and innovation. The question of why some countries grow faster while some are lagged behind has ever been one of the debated topics. However, ICT adoption contributes to a broadening gap between the better-off and worse-off countries, which characterizes the unequal distribution across the world. Hence, this study aims to: (a) investigate the determinants of ICT adoption: (b) examine the influences of ICT adoption on economic growth: (c) identify the impact of ICT adoption on innovation. Two methodologies were used to achieve the objectives of the study. In the first objective, the study applies dynamic panel estimator GMM which covers 44 developed countries and 58 developing countries from 2008 until 2016. The result indicates that for all four types of ICT adoption (mobile broadband, fixed broadband, mobile telephone subscriptions and internet user) were highly correlated with income. Countries with more prosperity and prosperous populations tend to spend more on ICT products and services. However, the adoption of fixed broadband subscriptions and Internet user seems to decrease with the rise of income in developing countries. Higher education is essential to determine the ICT adoption in developed and developing countries. On top of that, the capacity of the countries to innovate is associated with ICT adoption in developing countries compared to developed countries. As for second objective, the study proceeds to examine the impact of ICT adoption on economic growth using the dynamic panel estimator GMM based on the data obtained from 2008 until 2016 covering both developed and developing countries. The analysis covers 44 developed countries and 45 developing countries using the Cobb-Douglas production function. The results suggest that for the type of ICT adoption; mobile broadband and mobile telephone subscriptions drive the economic growth for developed countries. Moreover, the findings indicate that human capital is associated with the high economic growth in developed countries. In developing countries, all types of ICT adoption (mobile broadband, fixed broadband, mobile telephone subscriptions and internet use) seem to have greater influence on economic growth. Besides, developed and developing countries have shown to have larger coefficients of labor and capital inputs which lead to faster growth. For the third objective, the study applies fixed-effect model based on the data spanning from 2008 until 2016 for 38 developed countries and 30 developing countries. The results indicate that high levels of Internet use are associated with high levels of ICT innovation in developed countries. Most of the wealthy countries, particularly, developed countries are actively rolling out ultrafast internet connections, and providing for the foundation innovations such as artificial intelligence, the Internet of Things, and Industry 4.0. As for developing countries, mobile and fixed broadband subscriptions are strongly influencing ICT innovation of the nation. It is believed that ultrafast broadband internet connections are becoming the critical foundation of boosting the digital economy in developing countries. In conclusion, countries with more wealth and prosperous populations are willing to adopt ICT. Compared with the older population, the young population students, tend to be more adventurous and highly demand for ICT specifically on the Internet. A good and innovative package of ICT offer might further promote the demand for ICT. The skilled and knowledge worker is essential to enable better adoption of new technology and implementing domestic innovation and influence the economic growth. In addition, good infrastructure network enables individuals and entrepreneurs engage in e-commerce, and businesses to manage their supply chains on cloud computing.